The Hepatoprotective Effect of Piperine Against Thioacetamide-Induced Liver Fibrosis in Mice: The Involvement of miR-17 and TGF-β/Smads Pathways - Abdelhamid, Amr M.; Selim, Ayman; Zaafan, Mai A. (Frontiers in Molecular Biosciences, 2021)
Liver fibrosis is characterized by a series of events including activation of quiescent hepatic stellate cells (HSC) into proinflammatory, contractile, and fibrogenic myofibroblasts which is the primary trigger for the fibrogenesis process. HSC activation involves many signaling pathways such as TGF-β/smads pathway. Specific microRNAs have been identified to play a crucial role in the activation of HSCs via various signaling pathways. Piperine has recently studied as a promising anti-fibrotic agent against pancreatic fibrosis through altering TGF-β1/Smad pathway. Hence, the current study evaluated the beneficial effects of piperine in thioacetamide-induced liver fibrosis in mice through the modulation of miRNA-17 and TGF-β/smads pathways. Mice were allocated into three groups randomly. Thioacetamide was used to induce liver fibrosis through 6 weeks. Starting from the fourth week of the experiment, mice were treated with piperine daily for 21 days. Piperine treatment resulted in a significant down-regulation of miRNA-17 expression, leading to the restoration of smad-7 accompanied with marked inhibition of TGF-β/smads signaling with further suppression of the activated HSCs and collagen deposition in the hepatocytes. In conclusion, piperine can be a promising therapeutic agent for treatment of liver fibrosis through inhibiting TGF-β/smads pathway.